(untitled) (Jalalabad Medical Journal, 2025)
Worldwide, lung cancer is the most common cause of major cancer incidence and mortality in men, whereas in women it is the third most common cause of cancer incidence and the second most common cause of cancer mortality. This study aimed to assess the findings of CT-guided fine needle aspiration cytology (FNAC) in diagnosing lung lesions. This cross-sectional observational study was conducted in the department of pathology in Jalalabad Ragib-Rabeya Medical College Hospital, from January 2023 to December 2023. A total of 60 patients with suspected lung masses were selected as study subjects. A purposive sampling technique was adopted in this study. Collected data were analysed using descriptive statistics. Analysis of data was carried out by using a statistical package for social science (SPSS) 22.0 for Windows. The study comprised 60 participants, predominantly male (76.67%). Most lesions were in the right lung (50%), with the right lower lobe most affected (21.67%). Squamous cell carcinoma (45%) was the most common cytological finding, followed by inflammatory lesions (18.33%). Cytologically, 70% were malignant, with 25% benign and 5% suspicious. Radiologically, 76.67% were malignant, and 23.33% were benign. Complications of CT-guided FNAC included pneumothorax (3.33%), minor bleeding (3.33%), haemoptysis (1.67%), and infection (1.67%). This study concludes that CT-guided FNAC is a highly effective and safe diagnostic tool for diagnosing lung lesions. It aids in differentiating between benign and malignant lung lesions and also helps in the diagnosis of different types of lung cancers. Jalalabad Med J 2024; 21 (2); 68-72